2016
DOI: 10.3389/fncel.2016.00193
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Taste Signaling in Drosophila Larvae

Abstract: The Drosophila larva has a simple peripheral nervous system with a comparably small number of sensory neurons located externally at the head or internally along the pharynx to assess its chemical environment. It is assumed that larval taste coding occurs mainly via external organs (the dorsal, terminal, and ventral organ). However, the contribution of the internal pharyngeal sensory organs has not been explored. Here we find that larvae require a single pharyngeal gustatory receptor neuron pair called D1, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 92 publications
(180 reference statements)
3
35
0
Order By: Relevance
“…In a previous study, we found that a specific pair of neurons in the dorsal pharyngeal sensilla called DP1 is necessary and sufficient for caffeine-mediated decrease in ingestion (Choi et al, 2016). An independent study found that the same neurons mediate caffeine avoidance (Apostolopoulou et al, 2016). The DP1 neuron expresses the Gr33a-, Gr39b-, and Gr22d-GAL4 drivers (Choi et al, 2016).…”
Section: Dp1 Neurons Are Necessary and Sufficient For Caffeine-inducementioning
confidence: 97%
“…In a previous study, we found that a specific pair of neurons in the dorsal pharyngeal sensilla called DP1 is necessary and sufficient for caffeine-mediated decrease in ingestion (Choi et al, 2016). An independent study found that the same neurons mediate caffeine avoidance (Apostolopoulou et al, 2016). The DP1 neuron expresses the Gr33a-, Gr39b-, and Gr22d-GAL4 drivers (Choi et al, 2016).…”
Section: Dp1 Neurons Are Necessary and Sufficient For Caffeine-inducementioning
confidence: 97%
“…Defined ORN activation (standardized CS) can then be paired with activation of individual sensory neurons expressing gustatory receptors, ionotropic receptors, transient receptor potential cation channels, and/or pickpocket ion channel genes ( Clyne, 2000 ; Dunipace et al, 2001 ; Scott et al, 2001 ; Liu et al, 2003 ; Montell, 2005 ; Benton et al, 2009 ). In this manner, one could comprehensively identify the sensory neurons that encode for appetitive and aversive reinforcement in Drosophila larvae (e.g., Gr93a for aversive reinforcement and IR60c potentially for appetitive reinforcement) ( Apostolopoulou et al, 2016 ; Croset et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the actual stimuli can only be confirmed by physiological and behavioral tests. Indeed, few studies have defined a link between gustatory stimuli and particular neurons of the TO (Apostolopoulou et al, ; Apostolopoulou et al, ; Apostolopoulou et al, ; van Giesen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The terminal organ (TO) lies close and ventrally to the dorsal organ (DO). Below, the mouth hooks are visible above the mouth opening (modified from Apostolopoulou et al, ). Cuticle cirri (cirri) cover the frontal part of the cephalic lobes.…”
Section: Introductionmentioning
confidence: 99%